ANALISA PERBANDINGAN DIFERENSIASI PRODUK PADA RADUSA.CO DAN MAPLE_ID - Merita Bernik; Thifal Al thavia Dwinandita (Jurnal Manajemen Industri dan Logistik, 2017)
In Indonesia the fashion business developments take place quite rapidly. Along with the increased efforts in the field of fashion, causing competition among entrepreneurs engaged in the same field. Various strategies drawn up by the employers in order to win or retain its position as market leader. There are many businesses especially fashion handbags are such change or modify the appearance of the product. When talking about the uniqueness of bags for teenagers and adults may employers bag will compete to create innovative products to create a variety of sizes and colors, unlike the case with the children's work unique bags are bags production Radusa Company and Maple Indonesia. The objective of this study was to compare product  differentiation of Radusa Company and Maple Indonesia and to know that consumers have been able to identify well the product  differentiation that had been produced compared to their competitors The research method used is a mix method that is quantitative method and qualitative method, to be able to describe a certain condition about product differentiation at Radusa Company and Maple Indonesa. The sampling technique used is nonprobability sampling with purposive method, where the sample is the consumer who is at least 16 years old. For each company taken a sample of 30 consumers. The results of this study indicate that the outline of Radusa Company has differentiated the product in terms of shape, quality of performance, suitability of quality, durability, reliability, ease of improvement and style. While Maple Indonesia has a differentiation of products viewed from the form, features, quality performance, quality conformance, durability, reliability, ease of improvement and style. Based on the respondent's statement about the comparison of product differentiation and Wilcoxon test, it is found that Radusa Company is better than Maple Indonesia